TATA KELOLA BADAN USAHA MILIK DESA DENGAN PERSPEKTIF GOOD GOVERNANCE (BUMDES SUMBER SEJAHTERA) DI DESA GENITO, KECAMATAN WINDUSARI, KABUPATEN MAGELANG - Dedek Setiawan; Risma Wira Bharata (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This research aims to determine the implementation of Village Owned Enterprises (BUMDes) governance with the perspective of Good Governance at Sumber Sejahtera BUMDes in Genito Village. The village founded BUMDes as a legal body to manage enterprises, utilize assets, develop investment and production, and offer services for the welfare of rural communities. Meanwhile, good governance is a set of practices used to make choices in both commercial and public organizations. The qualitative method was applied in this study. In this study, the researchers applied three theories: people's welfare, decision-making processes, and policy implementation governance. The study results demonstrate that People's Welfare, under the management of BUMDes Sumber Sejahtera in Genito Village, is in compliance with the people's welfare principle, namely that all BUMDes actions are centered on boosting community economic productivity. Decision Making Process, all choices in the management of the Sumber Sejahtera BUMDes are determined after deliberation in order to establish a mutual agreement for mutual prosperity. Policy Implementation Procedures, there is a management structure in the management of the Sumber Sejahtera BUMDes, each of which is responsible for executing policies at the BUMDes.